The Role of Paradiplomacy in the Development of the Aruk Border Area - Rachmawati, Iva; Mohamad Pero, Siti Darwinda; Wirawan, Muhammad Ridho (Journal of Paradiplomacy and City Networks, 2022)
Being isolated and lacking public facilities, border areas tend to be neglected. On the other hand, border areas can serve as economic and social hubs if isolation is broken through development and international cooperation. The Aruk border area in Sambas Regency was extremely underdeveloped before the construction of the Aruk Cross-border Post (PLBN). Opening the remoteness of Aruk was a challenging endeavor. However, through the local government’s efforts, Aruk has become one of the wheels of the economy in Sajingan Besar District, Sambas Regency. Using the concepts of the formal and informal roles of paradiplomacy in transborder diplomacy, this article reviews how paradiplomacy attempts to open up the isolation of Aruk for the welfare of the people at the border. This qualitative research discovered that the roles of formal and informal paradiplomacy in Sambas have significantly affected the development of the regency. Formal relationships have been held in the KK Sosek Malindo, while informal relationships have been built by personal relationships owned by regional sub-national actors. The two relations have encouraged the birth of policies supporting the border area’s development in Aruk.